Effects of Online Prenatal Yoga on Anxiety Level and Quality of Life Among Third Trimester Pregnant Women in North Cikarang District - Bambang Amelia Fajriati Urbaningrum; Akhmad Yogi Pramatirta; Puspa Sari; Hadi Susiarno; Vita Murniati Tarawan; Shelly Iskandar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
The third trimester of pregnancy, is a vulnerable period for anxiety due to physical changes, sleep disturbances, hormonal shifts, and concerns about childbirth. According to statistics from the WHO, up to 10% of pregnant women and 13% of postpartum women suffer from mental health problems, among which the prevalence of prenatal anxiety is as high as 15%. These conditions may impair maternal and fetal health and reduce quality of life. Prenatal yoga, especially movements targeting the psoas muscle, has been proposed to alleviate stress and anxiety. This study aimed to examine the effects of prenatal yoga on anxiety levels and quality of life among women in the later stages of pregnancy in North Cikarang District. A total of 64 participants took part in this quasi-experimental study. They were allocated into two groups based on health centers: an intervention group (n=32), which received eight online prenatal yoga sessions, and a control group (n=32), which continued routine antenatal care. To assess the impact of the intervention, anxiety levels were evaluated both before and after the treatment using the “Perinatal Anxiety Screening Scale (PASS)”, and quality of life was measured using the “World Health Organization Quality of Life Scale-Brief (WHOQOL-BREF)”. Data analysis was performed using the Wilcoxon and Mann-Whitney statistical tests. The findings revealed a significant decrease in anxiety levels among participants in the intervention group compared to those in the control group (p < 0.001). Furthermore, participants who engaged in prenatal yoga experienced notable enhancements in their quality of life, encompassing physical, psychological, social, and environmental aspects (p < 0.001). Overall, the study concludes that prenatal yoga serves as an effective approach to alleviating anxiety and enhancing the overall quality of life for women in the later stages of pregnancy in North Cikarang District Keywords: Anxiety, Third-Trimester Pregnancy, Quality of Life, Pregnant Women, Online Prenatal Yoga